Sub-Volt Bulk-Driven Transconductance Amplifier and Filter Application - Kumngern, Montree; Torteanchai, Usa; Yutthanaboon, Sathian; Khateb, Fabian (My University, 2018)
This paper describes a low-voltage and low-power transconductance amplifier and its application to third-order elliptic low-pass filter. The bulk-driven MOS transistor technique is used to provide low supply voltage operation and rail-To-rail input voltage common mode. The performance of the proposed filter is expressed through PSPICE simulators using TSMC 0.18 μm n-well CMOS process. Simulation results show that the filter using proposed circuit consumes 36 μW for power supply of a 0.5 V and has total harmonic distortion 1 % for input signal of 480 mVP-P.
Keywords: analog circuit; bulk-driven MOS transistor; elliptic low-pass filter; transconductance amplifier